Jurnal Dialektika Kontemporer Beranda Tentang Kami Beranda Pengguna Cari Terkini Arsip Tesis Abstrak Beranda > volume 1 nomor 1 Tahun 2013 > Rongrean DINAMIKA SOSIAL PRAMURIA ( Studi Kasus di Pharos Nite-Park, Makassar) - Benyamin Rongrean (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
The choice to become a nightclub hostess arises from conflicts at home. The situation forces a woman to find a job just to run away from the issues surrounding her weight. Disappointment to the family environment causes the informants escape in order to meet the needs of their dependents. They had had no options but to obtain money instantly as prostitutes. External factors such as friends and family environment also contribute to their decisions.Keywords: Social Dynamics, Nightclub Hostess, Environment